Using GOFER to Digitize Patient Records in Kathmandu Model Hospital - Pradhan, Hema Kumari; Dangal, Ganesh; Karki, Aruna; Shrestha, Ranjana; Bhattachan, Kabin; Poudel, Rekha; Bajracharya, Nishma; Tiwari, Kenusha; Cochran, Seth; Michaelson, Bryony (Nepal Journal of Obstetrics and Gynaecology, 2018)
Aim: To collect and digitalize data of patients who underwent fistula repair at Kathmandu Model Hospital. Methods: Operation Fistula built a digital version of Model Hospital’s Surgery Log, using a mobile data collection tool (Commcare). Researchers were trained on the data collection tool and provided with a tablet which hosted the application. Once data is collected, tableau dashboard will be built to visualize the collected data and to share key insights. Model Hospital then proceeded to input patient records, and provided Operation Fistula with key feedback to continue improving this process. Results: The results of this process have been threefold: Facilitation of data collection, Creation of an accurate database, and Provision of clear insights with access to data visualization dashboards. Conclusions: This study has shown the benefits of digitizing historical patient records using GOFER. By creating an online database, this has the potential to be used in future for academic research.